Fisheries Research - Fisheries Research (Elsevier, 2026)
An International Journal on Fisheries Science, Fishing Technology and Fisheries Management This journal provides an international forum for the publication of papers in the areas of fisheries science, fishing technology, fisheries management and relevant socio-economics. The scope covers fisheries in salt, brackish and freshwater systems, and all aspects of associated ecology, environmental aspects of fisheries, and economics. Both theoretical and practical papers are acceptable, including laboratory and field experimental studies relevant to fisheries. Papers on the conservation of exploitable living resources impacted by fisheries are welcome. Review and Viewpoint articles are also published. As the specified areas inevitably impinge on and interrelate with each other, the approach of the journal is multidisciplinary, and authors are encouraged to emphasise the relevance of their own work to that of other disciplines. The journal is intended for fisheries scientists, biological oceanographers, gear technologists, economists, managers, administrators, policy makers and legislators.
FI 0.88
Q2
Keywords: Agriculture; Aquaculture & Food Science; Aquaculture; Fisheries & Fish Science; Acuicultura; Ictiología; Acuerdos transformativos; Transformative agreements; Gestión pesquera; Tecnología pesquera; Pesca